2020
DOI: 10.1007/s42452-020-03369-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the inclusion of industrial and agricultural wastes on the compaction and compression properties of untreated and lime-treated clayey sand

Abstract: The reuse of industrial and agricultural wastes is an alternative method to provide low-cost building materials for the construction industry and reduce the environmental pollutions. This study evaluates the feasibility of using a couple of waste materials including palm fiber, palm fiber ash and fiber bundles both individually and in combination with lime to improve strength characteristics of clayey sand. A series of laboratory tests were performed on samples cured for 7, 14, 28 and 56 days to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In recent decades, researchers and engineers have proposed numerous methods for the improvement of the mechanical properties of soils through mechanisms that are more environmentally friendly [40][41][42][43], i.e., the use of polypropylene [44], tire strips [45], crushed tires [46]; as well as the addition of artificial and natural fibers, such as fiberglass [7], coconut shell [47,48]; water hyacinth [49], palm fibers [50], jute [51], Kernel palm shells [5]; rice husk ash [52]. Similarly, some research has been observed on the use of electronic waste (e-waste) in activities to improve the engineering properties of soils [53,54].…”
Section: Of 25mentioning
confidence: 99%
“…In recent decades, researchers and engineers have proposed numerous methods for the improvement of the mechanical properties of soils through mechanisms that are more environmentally friendly [40][41][42][43], i.e., the use of polypropylene [44], tire strips [45], crushed tires [46]; as well as the addition of artificial and natural fibers, such as fiberglass [7], coconut shell [47,48]; water hyacinth [49], palm fibers [50], jute [51], Kernel palm shells [5]; rice husk ash [52]. Similarly, some research has been observed on the use of electronic waste (e-waste) in activities to improve the engineering properties of soils [53,54].…”
Section: Of 25mentioning
confidence: 99%
“…In this same category, 24% of the studies in the period 2004 to 2021 used AWBs as a total and/or partial substitute material for conventional fine and/or coarse aggregates in concrete [21,28,29,36,66,67,83,[89][90][91][92]. A smaller percentage (3%), between 2019 and 2021, analysed the potential of AWBs as additives and/or aggregates for soil stabilisation and/or improvement of geotechnical properties [69,70,93]. Other studies used a similar classification for the categories of use of agricultural residues in concrete [15,66].…”
Section: Main Approaches To Scientific Production-systematic Reviewmentioning
confidence: 99%
“…In addition, in other applications used to improve the thermal performance of buildings (21-63%) [23,58]. On the other hand, lower AWB percentages (2-4%) were considered for soil stabilisation [70,93]. 4, several of the studies analysed point out some limitations and/or disadvantages derived from the use of AWBs as biomaterials for the production of bio-based products.…”
Section: Main Types and Properties Of Awbs Used By Categorymentioning
confidence: 99%
“…In recent decades, researchers and engineers have proposed numerous methods for the improvement of the mechanical properties of soils through mechanisms that are more environmentally friendly [40][41][42][43], i.e., the use of polypropylene [44], tire strips [45], and crushed tires [46], as well as the addition of artificial and natural fibers, such as fiberglass [7], coconut shell [47,48], water hyacinth [49], palm fibers [50], jute [51], kernel palm shells [5], and rice husk ash [52]. Similarly, some research has been observed on the use of electronic waste (e-waste) in activities to improve the engineering properties of soils [53,54].…”
Section: Introductionmentioning
confidence: 99%